A practical seasonal performance evaluation of small wind turbine in urban environment. Issue 4 (August 2019) - Rajab, Zakariya; sassi, Yousef; Taher, Ahmed; Khalil, Asharf; Mohamed, Faisal
Due to the low environmental impact, smaller storage units, low wind speed, low power system distribution network impact, and low maintenance, small wind turbines have gained more attention. However, the usage of small turbines usually faces several shortcomings, and the actual yield is often lower than expected, generally because the output power is low when compared with the manufacturer, and the actual wind turbine behavior does not reproduces. In a view of performance evaluation of a small wind turbines using high-accuracy measurement devices to measure wind speed and energy production, this article illustrates an experimental seasonal performance evaluation of a 0.5-kW Hummer small wind turbine, placed in an urban environment. In addition, we study the influence of the height in the energy output and analyze its effect in the system performance, which is another aim in this work. Three cases have been carried out: 4 m in order to protect rotor blades during strong winds and storms in the first scenario and 6 m the manufacturing height in the second scenario while 10 m the third case. A 0.5-kW Hummer wind turbine has been installed in Noagia-Benghazi since 2010 for educational purposes, field studies, training, graduate projects, and research. The wind turbine seasonal performance under different periods was obtained and compared in terms of the wind speed, output power, energy production, and average wind speed. The average wind speed is 6.4, 4, 5.8, and 4 m/s, and the average energy production is 948.24, 172.8, 648, and 172.8 kWh in spring, summer, winter, and autumn, respectively. Spring has the highest wind speed followed by winter and autumn then summer for all height. Improvement is attained if the wind turbine tower height is 6 m, and 10 m where more energy is harvested. But the main problem at 10 m is that the system control needs more improvement because the wind speed exceeds 14 m/s which represents the maximum speed. The system can produce about 1.942 MW yearly and save CO2 emissions.